Por este oído me entra (o el arte de leer en voz alta) (Journal of Parents and Teachers, 2014)
The article gathers a series of guidelines and resources related to reading aloud in the classroom. Therefore, the author describes some aspects that should be taken into account during reading as well as some variations to do it correctly.
Keywords: Reading outloud; Storytelling; resources; Education